Coupled Dufour and Soret Effects on Hybrid Nanofluid Flow through Gyrating Channel Subject to Chemically Reactive Arrhenius Activation Energy - Raizah, Zehba; Khan, Arshad; Gul, Taza; Saeed, Anwar; Bonyah, Ebenezer; Galal, Ahmed M. (Journal of nanomaterials, 2023)
This study explores the magnetohydrodynamic fluid flow through two rotating plates subjected to the impact of microorganisms. The nanoparticles of copper and alumina are mixed with water for formulating hybrid nanofluid with new combination Cu+Al2O3+H2O. This new combination augments the thermal conductivity of pure fluid. The flow is influenced by the coupled effects of Dufour and Soret diffusions. The joined effects of chemically reactive activation energy have been incorporated in the mass transportation equation. A constant magnetic field has been employed to the flow field with strength B0 in normal direction to the plates. The equations that controlled fluid flow have been transferred to dimension-free form by implementing suitable set of variables. The influence of the different factors has been examined theoretically by employing the graphical view of different flow profiles. It has been concluded in this work that, linear velocity has declined by augmentation in magnetic factor and rotational parameter whereas these factors have enhanced microrotational profiles of fluid. Higher values of radiation parameter, Dufour number, and volumetric fractions have augmented fluid’s thermal profiles. The concentration of fluid has been retarded with upsurge in Soret number and chemical reaction parameter whereas growth in activation energy parameter has supported the upsurge in concentration. The rate of motile microorganisms has retarded by upsurge in the values of Lewis and Peclet numbers. It has been noticed that when Kr, M, and Re varies from 0.2 to 0.6 then in case of nanofluid, skin friction changes from 0.288 to 0.633 at ϕ1=0.01 and from 0.292 to 0.646 at ϕ1=0.02 and in case of hybrid nanofluid the variations in skin friction are from 0.328 to 0.646 at ϕ1, ϕ2=0.01 and from 0.335 to 0.703 at ϕ1, ϕ2=0.02.